IMPLEMENTASI PROGRAM JAMINAN PERSALINAN DI PUSKESMAS NGESREP KOTA SEMARANG DITINJAU DARI ASPEK KEPESERTAAN - Dwi Indra Jaya; Tri Yuniningsih; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Security Childbirth Program is an extension of membership of Public Health Security Program and includes not only the poor alone. Benefits received by beneficiaries Security Childbirth Program is limited to pregnancy care, delivery, postpartum, newborn and postpartum family planning. Management of Security Childbirth Program done at every level of government (central, provincial, and district / city) which is an integral part of the Security Childbirth Program and managed to follow the governance of Public Health Security Program. The purpose of this study is to describe and analyze the implementation of the PHC Ngesrep Security Childbirth Program in Semarang viewed from membership aspects. This study used a qualitative descriptive type using the informan of the City Health Office of Semarang, Ngesrep Public Health Center, Independent Practice and Community Midwives. Model Implementation Van Horn and Van Metter used to analyze the implementation of the Security Childbirth Program At PHC Ngesrep Semarang. The results showed that the Security Childbirth Program in Semarang for this is still in compliance and equity of health personnel and facilities. The main objective to reduce MMR and IMR is still not achieved even no trend of increased MMR and IMR. There is a weakness in the claims payment process Jampersal program which resulted in delays in the disbursement of claims. The delay will affect the income of the Independent Practice Midwife working with the government to serve the patient, the program imposes costs Security Childbirth Program but rather the fact that participants did not conform Security Childbirth Program Technical Instructions. Researchers advise that funding claims each month on an ongoing basis, the increase in the amount of claims service delivery, increase the number of midwives and providing standardized ambulance to transport for referral of patients in emergency cases.